Current resting metabolic rate prediction equations lack sensitivity and specificity to indicate relative energy deficiency in sport: A large cohort study in elite athletes - Heikura, I. A.; Tsai, M.-C.; Sesbreno, E.; McCluskey, W. T. P.; Johnson, L.; Murray, H.; Stellingwerff, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Objectives: Measured resting metabolic rate (RMR) was compared to predicted RMR equations (RMRratio) to see whether a low RMRratio relates to the Relative Energy Deficiency in Sport (REDs) Clinical Assessment Tool 2 (CAT2) severity/risk score.